Conserving orangutans one classroom at a time: evaluating the effectiveness of a wildlife education program for school‐aged children in Indonesia. (15th May 2019) - Freund, C. A.; Achmad, M.; Kanisius, P.; Naruri, R.; Tang, E.; Knott, C. D.
Abstract: Environmental education is a cornerstone of many wildlife conservation programs, and measuring the impact of such education initiatives is imperative for evaluating their effectiveness in achieving conservation goals. For over 15 years, the Gunung Palung Orangutan Conservation Program (GPOCP) has been working to protect wild Bornean orangutans Pongo pygmaeus wurmbii living in and around Gunung Palung National Park in West Kalimantan, Indonesia. In 2015, we carried out a series of six Environmental Education Expeditions to communities in the remote districts surrounding the Park, engaging 1519 elementary ( n = 770) and junior/senior high school ( n = 749) students across 24 schools. Before and after engaging with our environmental education activities students were given surveys to assess their knowledge about and attitudes toward orangutans. We found that our educational activities led to 13.6–40.4% increases in student knowledge about orangutans and substantial shifts toward more positive attitudes about conservation, but that many students do not believe that they personally can make a difference. Empowerment may be a key need to link wildlife education to environmental action. Abstract :